2015
DOI: 10.1186/s40886-015-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Goniometer-apps in hand surgery and their applicability in daily clinical practice

Abstract: Background: Smartphones have become an integral part of our daily lives, and numerous applications (apps) make use of the goniometer, which is comparable to a medical protractor. The aim of this study was to evaluate the availability, reliability and validity of medical apps using the goniometer function in smartphones. Methods: Sixteen goniometer-apps downloaded from Apple's (twelve apps) and Google's (four apps) app stores matched initial inclusion criteria (inclusion criteria: *gonio* or *rom*, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
12
0
1
Order By: Relevance
“…With the aim of investigating differences among applications and operating systems, Kuegler et al [27] compared the angular measurements of sixteen goniometric applications and two different operating systems using an irregular pyramid-shaped object with four sides and consequently four different angles. The applications performed in a similar manner for all measurements, with minimal variation; the iOS (operating system of Apple) had a maximum angular variation of 1.8°, and the Android (operating system of Google) presented a maximum angular variation of 1.3°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of investigating differences among applications and operating systems, Kuegler et al [27] compared the angular measurements of sixteen goniometric applications and two different operating systems using an irregular pyramid-shaped object with four sides and consequently four different angles. The applications performed in a similar manner for all measurements, with minimal variation; the iOS (operating system of Apple) had a maximum angular variation of 1.8°, and the Android (operating system of Google) presented a maximum angular variation of 1.3°.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al [11], Alba-Martín [15], and Johnson et al [16] found excellent intra-and inter-examiner reliability for measurements of the range of motion of the shoulder in different positions using the Clinometer A large number of applications are available for measuring joint range of motion. Some can be used for any joint, whereas others are dedicated for specific joints [27]. Applying similar methodology as that employed in the present study, Milanese et al [6] evaluated a specific application for the knee: Knee Goniometer App © , KGA (Apple iPhone…”
mentioning
confidence: 99%
“…Several authors have found comparable results using similar apps for other joints such as wrist [23], fingers [8,9], shoulder [24,25], lumbar spine [26], or even to analyze range of motion in patients who have suffered a stroke [27].…”
Section: Discussionmentioning
confidence: 78%
“…Kuegler et al (28) compared 15 applications for two operational systems to evaluate the reliability and validity of these applications regarding ROM in individuals in the postoperative period following hand surgery. Fourteen applications proved to be reliable and valid, but, according to the literature, these applications are not used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%